Physicochemical and Microbial Diversity Analyses of Indian Hot Springs - Narsing Rao, Manik Prabhu; Dong, Zhou-Yan; Luo, Zhen-Hao; Li, Meng-Meng; Liu, Bing-Bing; Guo, Shu-Xian; Hozzein, Wael N.; Xiao, Min; Li, Wen-Jun (Frontiers in Microbiology, 2021)
In the present study, phyisco-chemical and microbial diversity analysis of seven Indian hot springs were performed. The temperature at the sample sites ranged from 32 to 67 °C, and pH remained neutral to slightly alkaline. The pH and temperature influenced microbial diversity. Culture-independent microbial diversity analysis suggested bacteria as the dominant group (99.3%) when compared with the archaeal group (0.7%). Alpha diversity analysis showed that microbial richness decreased with the increase of temperature and beta diversity analysis showed the clustering based on location. A total of 131 strains (divided into 12 genera and four phyla) were isolated from the hot spring samples. Incubation temperatures of 37 and 45 °C and T5 medium were more suitable for bacterial isolation. Some of the isolated strains shared low 16S rRNA gene sequence similarity, suggesting that they may be novel bacterial candidates. Some strains produced thermo-stable enzymes. Dominant microbial communities were found to be different depending on culture-dependent and -independent methods. Such differences could be attributed to the fact that most microbes in the studied samples were not cultivable under laboratory conditions. Culture-dependent and -independent microbial diversities suggest that these springs not only harbour novel microbial candidates but also produce thermo-stable enzymes and hence, appropriate methods should be developed to isolate the uncultivated microbial taxa.